USE, MEANING AND FUNCTION OF IDOMA MARITAL PROVERBS - Amali, Halima Idris (Proverbium - Yearbook, 2015)
The main thrust of this paper is to analyze selected marital proverbs in Idoma. These are proverbs which relate to issues in marriage and that directly and indirectly apply to other situations in human life. It discusses the functional appreciation of each proverb and the lesson that an individual or the community stands to gain from these proverbs. Ten Idoma marital proverbs are translated and analyzed from the functional point of view. In this light, the paper examines appropriate application of the proverbs with focus on the lessons derived from each. Marital proverbs are applicable in varying situations in the family and the society in general. Such situations are in relationships between men and women, children in the family and in the community siblings, friends, relations and neighbours. This suggests therefore that marital proverbs are useful in many situations in and outside the family, as well as in the community at large and can be applied in situations of misunderstanding for amicable resolutions.